Recursos retóricos para a realização da persuasão implícita em textos argumentativos: um enfoque crítico da Linguística Sistêmico-Funcional - Cantanhede, Caio Silva Sousa (2016)
The goal of this master’s dissertation is the critical examination of the rhetorical resources used in the argumentations to accomplish the persuasion implied in a newspaper editorial. The argumentation belongs to the Family of human actions which objective is to persuade through the conviction or seduction. However the rhetorical of the persuasion requires that the interlocutors should be convinced that were not convinced, and like that, the persuasion tends to be highly implicit. Through the history, the appropriate way of studying the argumentation has been debate for several philosophical traditions, including the formal logic; however, it has raised certain issues when applied to the argumentation of the real life. The informal logic, or pragmaticsdialectic – on the other hand, is an approach relatively recent that focuses in arguments of the real life. It includes pragmatics intra views with the dialectics and emphasizes the rhetorical factors importance in argumentation and persuasion of people, showing the effectiveness of the argument in centered factors in hearing. Since the cognitive pragmatic point of view, the meaning goes further – is the recovery of the intentional information, and not or not only the action social standards. The research supported in the linguistics systemic-functional, a multifunctional theory indicated like be appropriated to the critic’s speech analysis. The editorial’s analysis shows that the implicit persuasion occurs in the underlay of the text and that to its revelation is necessary the focus in the relationship among the lexicon-grammatical choices made in the microstructure of the text with the values, which are in the macrostructure of the speech. The research aims to answer the following questions. (a) How is the structure of an argumentation? How it starts, how is perceived, developed and how it ends? (b) What is the roll of the way to evaluate in the persuasion, coursing the editorial? (c) How is made the implicit persuasion?